Improving patient reported outcome measures (PROMs) in total knee replacement by changing implant and preserving the infrapatella fatpad: a quality improvement project. Issue 1 (5th May 2016) - Partridge, Thomas; Carluke, Ian; Emmerson, Kevin; Partington, Paul; Reed, Mike
Abstract : Patient reported outcome measures (PROMs) were introduced in 2009 to allow patient perspectives to potentially influence change and improvement. In collaboration with the national joint registry (NJR), PROMs data has been examined on a national basis to compare surgical factors in total knee replacement (TKR). Initial results demonstrated there were statistically significant differences in Oxford Knee Score (OKS) when using different brands of implant. Preservation of the infrapatella fatpad (IFP) has also been shown improve outcomes. This led Northumbria Healthcare NHS Foundation Trust to make a mass move to the Zimmer Nexgen TKR and later change surgeons' routine practice to preserving the IFP. The PROMs were recorded pre and six months post operation to obtain improvement scores. The baseline improvement in OKS was 14.0. After changing implant to the Zimmer Nexgen in Plan-Do-Study-Act (PDSA) cycle 1 the average improvement score was 16.7. After implementing default preservation of the IFP in PDSA cycle 2 the average OKS improvement score was 17.3. The results from this project demonstrate a significant improvement in local services after implementing changes based on national and local evaluations. This initiative is an excellent example of improvement by evidence based practice and success of the English National Health Service PROMs scheme.